2014
DOI: 10.1111/raq.12056
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing GAABAP shrimp farm data to determine whether certification lessens environmental impacts

Abstract: The sustainable seafood movement is over a decade old. It has done much to raise awareness regarding improper production and harvest of seafood and to derive a course to lessen the deleterious environmental impacts of this industry. Certification has been a key tool, yet few programmes have demonstrated comprehensive improvements. Here, the degree of aquaculture improvement through the implementation of certification was assessed using data from the Global Aquaculture Alliance (GAA) Best Aquaculture Practice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Prior to the establishment of the ASC, the Global Aquaculture Alliance (GAA) emerged in 1997 in response to the environmental pressures and impacts of aquaculture on marine species and their habitats (Kalfagianni & Pattberg, 2013b). As it evolved, the GAA developed more rigorous assessment criteria known as Best Aquaculture Practices (BAP), which are standards that seek to raise the environmental and social quality of farms by defining the most important elements of responsible aquaculture (Tlusty & Tausig, 2014). Each BAP standard was developed by a committee of technical, environmental, and social experts and stakeholders (e.g., members of NGOs, industry, and academia).…”
Section: Global Aquaculture Alliancementioning
confidence: 99%
“…Prior to the establishment of the ASC, the Global Aquaculture Alliance (GAA) emerged in 1997 in response to the environmental pressures and impacts of aquaculture on marine species and their habitats (Kalfagianni & Pattberg, 2013b). As it evolved, the GAA developed more rigorous assessment criteria known as Best Aquaculture Practices (BAP), which are standards that seek to raise the environmental and social quality of farms by defining the most important elements of responsible aquaculture (Tlusty & Tausig, 2014). Each BAP standard was developed by a committee of technical, environmental, and social experts and stakeholders (e.g., members of NGOs, industry, and academia).…”
Section: Global Aquaculture Alliancementioning
confidence: 99%
“…The majority of studies evaluating impacts of seafood certification used reported statistics from standard holders (MSC and BAP) on progress against selected criteria to evaluate effects. For aquaculture farms, methodological challenges related to assessment of certification impacts are similar to those of other terrestrial agriculture systems; what little work has been done so far has documented changes in practices rather than performance . For capture fisheries, the most common indicator investigated is the status of the targeted stock (e.g., MSC principle 1), with studies largely ignoring impacts on non‐targeted species and the marine ecosystem (e.g., MSC principle 2), despite calls for their importance as a consideration on par with stock status .…”
Section: Es Information For Improving Evaluation Of Sustainability Stmentioning
confidence: 99%
“…For aquaculture farms, methodological challenges related to assessment of certification impacts are similar to those of other terrestrial agriculture systems; what little work has been done so far has documented changes in practices rather than performance. 86 For capture fisheries, the most common indicator investigated is the status of the targeted stock (e.g., MSC principle 1), with studies largely ignoring impacts on non-targeted species and the marine ecosystem (e.g., MSC principle 2), despite calls for their importance as a consideration on par with stock status. 53 Evaluating ecological effects of capture fisheries for eco-certification entails particular challenges given the dynamic nature of fish populations and some marine habitats and the relative difficulty of documenting, highlighting, and assessing the effects of gear on bottom habitats and of the direct and indirect effects of fishing on non-target species.…”
Section: Es Information For Improving Evaluation Of Sustainability Stmentioning
confidence: 99%
“…As in many food sectors, sustainability standards have emerged as a primary market-based assessment and assurance tool for 'sustainable' aquaculture production [1,2]. There are currently more than 30 aquaculture standards available, ranging from certification schemes to recommendation lists, and representing a diverse set of claims related to food safety, quality, traceability, environmental and social impact [3].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of sustainability standards depends to a large extent on the voluntary compliance of producers to their principles and indicators. This means that farmers are required to change their farming practices, farm management systems and/or shared water infrastructure between farms to meet the expectations prescribed within these principles and indicators [2,5]. However, standard setters neither discriminate nor differentiate between producers based on their ability to make any improvements necessary for compliance.…”
Section: Introductionmentioning
confidence: 99%